Imprensados no tempo da crise : a gestão das afetações no desastre da Samarco (Vale e BHP Billiton) e a crise como contexto no território tradicionalmente ocupado na foz sul do rio Doce - Flávia Amboss Merçon Leonardo (2022)
The rupture of the mining tailings dam in the city of Mariana, MG, in 2015 and the carriage of these tailings to the Rio Doce bed engendered a crisis in several affected municipalities in the states of Minas Gerais and Espírito Santo. Among the affected regions, this thesis analyses the coastal area of the state of Espírito Santo, where the southern mouth of the Rio Doce is located. The socio-technical disaster is understood as a critical moment in the lives of the residents in Regência Augusta and the adjacent villages, engendering changes in the daily life of the locality, even before the tailings reached its surroundings. With the arrival of the mud and the passing of time, the multiple effects of the disaster are heightened in the lives of residents. The damage caused by the disaster are experienced in the daily lives of the people involved as a chronic disorder. That is, it broadens situations of environmental conflicts previously experienced in that region. The thesis examines the institutional and corporate procedures adopted in the context of the Samarco (Vale and BHP Billiton) disaster in the Rio Doce, emphasizing the technologies deployed to crisis management and their effects among the residents in this traditionally occupied territory at the southern mouth of the Rio Doce.